EDTA-Fe(III) Fenton-like oxidation for the degradation of malachite green. (15th November 2018) - Hu, Yi; Li, Yulian; He, Junyong; Liu, Tao; Zhang, Kaisheng; Huang, Xingjiu; Kong, Lingtao; Liu, Jinhuai
Abstract: Industrial waste, urban sewage and aquaculture have led to severely increased grades of environment pollutants such as dyes, pesticides and fertilizer. The use of technologies for purifying contaminated waters can be difficult and toxic due to the anti-photolysis, anti-oxidation and anti-bio-oxidation characteristics of organic pollutants, and there is therefore a significant need for new approaches. Here, we report methods of Fenton oxidation and EDTA-Fe(III) Fenton-like oxidation which can be used to degrade malachite green (MG: a dye and antibiotic-like substance) from contaminated water. Compared with the degradation rate (59.34%) of the Fe(III)/H2 O2 Fenton process, the EDTA-Fe(III) Fenton-like oxidation got a better degradation rate (92.7%) at neutral pH conditions. By conducting a series of parallel controlled experiments (changing parameters such as the reactant concentration, temperature, and pH), we report the relationships between the degradation effect and different parameters, and we fitted their pseudo first order kinetic curves. Furthermore, we repeated to adjustment of the concentrations of MG in solutions to test the cycle performance and catalytic activities of EDTA-Fe(III)/H2 O2 system and it showed good repeatability in the first five rounds and all of them keep the degradation efficiencies greater than 80%. By conducting comparative spin-trapping electron paramagnetic resonance (EPR) experiments, we showed indirectly that the OH contributes to the degradation of MG. Additionally, the results of the EPR experiments showed that EDTA contributes to the generation of OH in the EDTA-Fe(III)/H2 O2 Fenton-like system. By conducting total organic carbon (TOC) analysis experiments, we found that EDTA was also oxidized to some extent during the degradation of MG. In all, the findings of this work widen the range of the optimal pH values up to neutral condition for degradation of MG by use of EDTA-Fe(III) Fenton-like system. And this system could be used as one approach for the degradation of organic pollutants at neutral conditions and provide some initial information regarding EDTA-Fe(III) Fenton-like oxidations. It's significant for the expansion of the homogenous Fenton-like family and its application in the field of water treatment. Graphical abstract: Image 1 Highlights: The feasibility of the Fenton-like system for MG degradation at neutral condition. Self-degradation possibility of EDTA in EDTA-Fe(III)/H2 O2 Fenton-like system. EDTA was contributed to the generation of OH in the Fenton-like oxidation. The mechanisms of EDTA-Fe(III)/H2 O2 Fenton-like oxidation.